Enhanced stability of simulated leukocytes for hematology internal quality control samples: A material improvement - Ngoc Nguyen Vo; Huu Tam Tran; Thi Thuy Nhu Le; Thi Hong Phuong Nguyen; Dinh Dung Vu; My Tran Thai; Thi Thanh Phung Nguyen (PLoS ONE, 2025)
Objectives This study aimed to develop and evaluate simulated leukocytes derived from porcine leukocytes as a stable alternative for internal quality control (IQC) in hematology laboratories. Addressing challenges related to material stability and availability, the research contributes to improving laboratory quality assurance in Vietnam. Methods Statistical methods including Shapiro-Wilk test, Levene’s test, t-tests, ANOVA, and the IQR method were applied to assess post-production quality and establish target values. Target values were established from data collected across 90 laboratories. The Interquartile Range (IQR) method was used to eliminate outliers, and target values were set for three analyzers (Sysmex XN-1000, Sysmex XN-550, and Horiba ABX Micros 60) per batch at three concentration levels. Sample stability was evaluated over a two-month shelf life using t-tests and monitored for 20 days post-opening with repeated measures ANOVA. Results Simulated leukocytes derived from goose erythrocytes exhibited instability at high concentration levels, whereas those derived from porcine leukocytes maintained stability over two months and demonstrated acceptable performance for up to 10 days post-opening. Conclusions The findings highlight the potential of porcine leukocytes as a reliable IQC material for hematology, meeting the stability and performance requirements of clinical laboratories.